Pollution, Ability, and Gender-Specific Investment Responses to Shocks. Issue 1 (11th March 2020) - Molina, Teresa
Abstract: This paper explores how labor market conditions drive gender differences in the human capital decisions of men and women. Specifically, I investigate how male and female schooling decisions respond to an exogenous change in cognitive ability. Using data from Mexico, I begin by documenting that in utero exposure to thermal inversions, which exacerbate air pollution, leads to lower cognitive ability in adulthood for both men and women. I then explore how male and female schooling decisions respond differentially to this cognitive shock: for women only, pollution exposure leads to reduced educational attainment and income. I show that this gender difference is explained by the fact that women disproportionately sort into white-collar jobs, where schooling and ability are more complementary than they are in blue-collar jobs.